Innovative techniques for concrete reinforcement with polymers. (1st June 2016) - Foti, Dora
Graphical abstract: Highlights: Concrete reinforced with PET bars and CFRP strips shows a higher ductility. PET bars and CFRP strips are inserted inside the concrete casting to make beam specimens. Bending tests are performed with a point load in the middle-span of each specimen. Comparisons of the results show a better behaviour of specimens with CFRP strips. Future tests with an equal area of reinforcement. Abstract: In this work the results of a series of preliminary tests on concrete beam specimens reinforced with PET and CFRP are shown and discussed. The novelty in the tests lies in the use of a waste material with promising results. The reinforcement is made with PET and CFRP are arranged as continuous bars and strips, respectively. They are positioned inside the specimen, in the same position of the steel bars in a reinforced concrete element. For both cases it is noticed that they limit the presence of cracks and, especially, avoid and/or reduce the corrosion processes in reinforced concrete structural elements. In particular, the concrete-fibers adhesion and the global behavior of these fiber reinforced concretes is analyzed in order to evaluate the possibility of future investigation. However, the results of the tests showed a better behavior for specimens reinforced with CFRP strips.